Physicochemical analysis of ion beam-induced surface modifications on polyethylene glycol films for liquid crystal alignment. Issue 12 (26th September 2019) - Lee, Ju Hwan; Won, Jonghoon; Jeong, Hae-Chang; Kim, Dong Hyun; Lee, Dong Wook; Han, Jeong-Min; Oh, Byeong-Yun; Seo, Dae-Shik
ABSTRACT: We investigated the surface modification induced by the ion-beam (IB) irradiation of a polyethylene glycol (PEG) film and its liquid crystal (LC) alignment characteristics. The X-ray photoelectron spectroscopy analysis revealed the chemical modification; as the IB incidence angle increased, the number of surface C–O bonds decreased, inducing an anisotropic dipole moment on the PEG film surface. In addition, the physical modification was demonstrated via atomic force microscopy analysis using three-dimensional images as a function of the IB incidence angle. The surface roughness was analyzed; the modification with the smoothest surface was observed for an IB incidence angle of 45°. This modification affected the LC alignment state of the PEG film, as demonstrated by the polarized optical microscopy analysis with pre-tilt angle measurements. Furthermore, for the same IB incidence angle, the residual DC measured using the capacitance–voltage curves was extremely low. Hence, a PEG film irradiated with an IB incidence angle of 45° could be a suitable LC alignment layer. Graphical Abstract: